2005
DOI: 10.1103/physrevb.72.235204
|View full text |Cite
|
Sign up to set email alerts
|

Negative capacitances in low-mobility solids

Abstract: The negative capacitance as often observed at low frequencies in semiconducting devices is explained by bipolar injection in diode configuration. Numerical calculations are performed within the drift-diffusion approximation in the presence of bimolecular recombination of arbitrary strength. Scaling relations for the characteristic frequency with bias, sample dimensions, and carrier mobilities are presented in the limits of weak and strong recombination. Finally, impedance measurements conducted on a light-emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 30 publications
2
68
0
Order By: Relevance
“…A negative differential capacitance (NDC) at voltages close to the built-in voltage has been reported from several studies of double-carrier devices. [11][12][13][14][15] These studies suggest that the effect results from the presence of a high-density nearly charge-compensated electron hole plasma in such devices. Various quantitative models have been proposed, involving a strong (more than one order of magnitude) reduction of the bimolecular recombination rate near the electrode interfaces, 12 a non-equilibrium population of interface trap states, 14 and trap-mediated recombination.…”
Section: Double-carrier Devicesmentioning
confidence: 93%
See 2 more Smart Citations
“…A negative differential capacitance (NDC) at voltages close to the built-in voltage has been reported from several studies of double-carrier devices. [11][12][13][14][15] These studies suggest that the effect results from the presence of a high-density nearly charge-compensated electron hole plasma in such devices. Various quantitative models have been proposed, involving a strong (more than one order of magnitude) reduction of the bimolecular recombination rate near the electrode interfaces, 12 a non-equilibrium population of interface trap states, 14 and trap-mediated recombination.…”
Section: Double-carrier Devicesmentioning
confidence: 93%
“…E.g., for the case r/(k B T) ¼ 3 or 6 a reduction of the recombination rate by a factor of 2.5 already reduces the capacitance to approximately zero or À2.3 C geom , respectively. Although it has been proposed that the recombination rate in organic semiconductors can be much smaller than as given by the Langevin formula, 12 recent Monte Carlo calculations have indicated that the Langevin formula holds well, albeit that it should be applied using so-called "bipolar" mobilities. In double-carrier devices the mobility is smaller than the single-carrier mobility due to the interaction with the randomly distributed carriers of the other type.…”
Section: Double-carrier Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been attemps to derive the minority carrier mobility from ac impedance using two-carrier models. 5,11 However, Poplavskyy and So 10 have reported evidence that the space-charge-related impedance response of dual-carrier diodes is dominated by combined electron-hole response, as proposed in the theory presented below.…”
Section: Introductionmentioning
confidence: 99%
“…10 Here we derive and discuss the impedance model of double injection SCLC in this case. We give an equivalent circuit explaining the impedance spectra at the low frequency limit for two-carrier devices 11 and compare it with the case of one-carrier device. There have been attemps to derive the minority carrier mobility from ac impedance using two-carrier models.…”
Section: Introductionmentioning
confidence: 99%